Penyelesaian Sengketa Konsumen Melalui Perdamaian Consumer Dispute Resolution Through Peace - I Made Agus Dwi Mandala Putra; I Nyoman Putu Budiarta; I Nyoman Subamia (Fakultas Hukum, Universitas Warmadewa, 2022)
The resolution of disputes between consumers and business actors is regulated in Law Number 8 of 1999 concerning Consumer protection, which stipulates that parties who will resolve consumer disputes can take litigation and non-litigation channels. The litigation channel is carried out through the general judiciary while the non-litigation route is through the Consumer Dispute Resolution Agency, utilizing mediation, conciliation, or arbitration. The formulation of the problem is how to arrange dispute resolution between consumers and business actors, and how is the legal force of peace deeds in disputes between consumers and business actors. The research method uses normative legal research, with sources of primary legal material and secondary legal material. The results of the study obtained that dispute resolution arrangements between consumers and business actors are regulated in law Number 8 of 1999 concerning Consumer Protection. With priority arrangements in resolving consumer disputes, it is through non-litigation channels by seeking peace between the parties with the principle of a win-win solution so that good relations between consumers and business actors are maintained.